Analysis of Islamic Cultural History (SKI) Learning Based on the Independent Curriculum - Muhammad Kafnun Kafi; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the evaluation of the Islamic Cultural History (SKI) learning process using the Merdeka Curriculum at MI Al Muhajirin Depok. The importance of understanding SKI for Indonesian students who are predominantly Muslim is the main highlight in this article. The research approach applied is descriptive qualitative which relies on observation, interviews and documentation as data collection methods. SKI learning at MI Al Muhajirin Depok is practiced with an aesthetic touch. Although the Independent Curriculum provides flexibility in adapting the curriculum, there are weaknesses related to consistency, quality standards and adequate supervision. Apart from that, this article offers several recommendations to improve SKI learning in these schools.